Analysis on Driving Effect of the Urbanization Development Speed on Water Resources Conflict. (24th January 2017) - Wu, Xiaoyuan; Xu, Changxin; Pang, Qinghua
Abstract : This paper aims to research the driving effect of the urbanization development speed on water resources conflict by building the risk stress coupling analysis model of urbanization development speed and water conflict. Firstly, we use the nonlinear fuzzy comprehensive adjustment (FCA) measure model based on entropy weight method to determine the level of urbanization and water resources conflict risk, then construct the coupling coordination degree function of urbanization speed and water conflict risk pressure, and calculate the coupling coordination degree. Secondly, we determine the level of water resources conflict according to the coupling coordination degree to obtain the trigger threshold value of water resources conflict and analyze the coupling results. Lastly, we start the instance analysis with Beijing City, Tianjin City, and Hebei Province region in Haihe river basin of China, as an example, by analyzing the influence of the urbanization speed on water resource conflict and by obtaining the threshold value of water resources conflict caused by the effect of water consumption of gross domestic product (GDP) per 10 thousand Yuan and annual per capita domestic water consumption on the urbanization development speed, expressed in interval number.